ANALISIS PERBANDINGAN DATA KUOTA INTERNET MUSIK STREAMING DENGAN RADIO STREAMING - Faisal Siregar; Suraya -; Suwanto Raharjo (Jurnal Jarkom, 2016)
Streaming Radio and Streaming Music is the audio playlists be heard exclusively live over the internet. In this case the end-users do not have to download it first and then save it on your computer, with this streaming end-users may request directly to the provider of the streaming service.Access music from streaming services is that many activities done by users on the internet today, either from music streaming services or from streaming radio service, but as the end-users they never knew whether the unused quota already fit or exceeding estimates. Therefore the author does an analysis and comparison of quotas against access music service that aims to find out the advantages and benefits that accrue to end-users against quota utilised in order to later quota can be set up efficiently in everyday use.